MAKNA KHITAN PEREMPUAN DALAM FILM PERTARUHANSEGMEN “UNTUK APA” - Nimas Dwi Safitri; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2014)
Feminism is one of issues which always talked about. It is a reason for a young director like Nia Dinata in Kalyana Shira Films Production House makes some documenter films about woman (feminism). One of them is Pertaruhan. In this film, there is 4 segmens, and in the second segmen has title “Untuk Apa?” raises about female circumcision. In this segmen there are many symbols and signs which has hidden meanings. Semiotic used to reveal that denotation sign of female circumcisionin this film is as an implementation of syari’ah Islam. Connotative sign in this film is female circumcisionas a tradition and culture in society. They believe that female circumcisionis one of legitimate terms for being a Moslem. Myths in this film is an animism culture in society, people’s belief that female circumcisionable to decrease number of cheating in marriage and able to give more satisfy to her partner when doing intimate relationship.